Clandestine Abortions in Cameroon: Risk Factors for Severe Complications - Nkwabong, Elie; Bechem, Efuetnkeng; Fomulu, Joseph Nelson (Bangladesh Journal of Obstetrics & Gynaecology, 2016)
Objective (s): The aim of this study was to identify risk factors for severe complications (SC) of clandestine abortions. Methods: This retrospective descriptive study was conducted between March 1st and August 31st, 2012 in the maternities of the University Teaching Hospital and the Central Hospital, Yaoundé (Cameroon). Files of women with clandestine abortions were recruited. Main variables studied were maternal age, parity, gestational age, the method used, the time interval between abortion and consultation, the complications presented. Data of women with SC were compared to those of women who had with non severe or no complications (NC). Fisher exact test and student t test were used for comparison. The significance level was p=0.05. Results: Amongst 94 women, 76 (80.9%) had SC against 18 (19.1%) with NC.Risk factors for SC were gestational age e12 weeks (OR 2.7, 95%CI 0.8-8.9), abortion carried out with dilatation and curettage/evacuation (OR 2.4, 95%CI 0.6-9.2) or with intramuscular injection of a non specified medication (four cases against zero respectively), by a nurse (OR 1.4, 95%CI 0.5- 4.1), by a friend (nine cases against zero respectively) or a traditional healer (three cases against zero respectively). Other risk factors were abortion carried out in a primary health center (OR 1.5, 95%CI 0.4-4.7) and late consultation after abortion (P=0.0404). Conclusions: For prevention of severe post abortal complications, women and abortionists should be informed on these risk factors. Bangladesh J Obstet Gynaecol, 2014; Vol. 29(1) : 21-25